Echocardiographic findings and subsequent risk of native valve endocarditis - Juan A. Quintero-Martinez; Joya-Rita Hindy; Hector R. Villarraga; Brian D. Lahr; Mark J. Dayer; Martin H. Thornhill; John C. O’Horo; Hector I. Michelena; Nandan S. Anavekar; Parham Sendi; Daniel C. DeSimone; Larry M. Baddour (Exploration of Cardiology)
Aim: The association of echocardiographic findings and subsequent risk of left-sided native valve endocarditis (LS-NVE) is undefined. The aim of this study was to determine if transthoracic echocardiography (TTE) measurements are associated with the subsequent development of LS-NVE in patients without cardiac predisposing conditions. Methods: Institutional databases were evaluated for adults diagnosed with LS-NVE from 2008 to 2020. Patients with prosthetic valves, cardiovascular implantable electronic devices, intracardiac devices, injection drug use, and predisposing cardiac conditions were excluded. Only patients who had a TTE performed 6 months to 3 years before the development of LS-NVE were included as cases. Controls were patients within the same Mayo location with a TTE report and were matched in a 1:3 ratio according to age, gender, Charlson comorbidity index, and echocardiography date. Results: There were 148 cases and 431 matched controls. As compared to controls, infective endocarditis (IE) cases had a higher prevalence of diabetes mellitus (46.6% vs. 30.4%) and chronic kidney disease (46.6% vs. 28.1%) (P < 0.001). Left ventricular outflow tract velocity (P = 0.017), left ventricular ejection fraction (P = 0.018), and E:e’ ratio (P = 0.050) were associated with LS-NVE. Conclusions: Echocardiographic measurements were associated with subsequent LS-NVE development in this pilot study. A larger cohort of LS-NVE patients, however, is needed to validate these findings.